Clostridioides difficile spore: coat assembly and formation. Issue 1 (31st December 2022) - Zeng, Ji; Wang, Hao; Dong, Min; Tian, Guo-Bao
ABSTRACT: Clostridioides difficile ( C. difficile ) is a Gram-positive, spore-forming, toxin-producing, obligate anaerobic bacterium. C. difficile infection (CDI) is the leading cause of healthcare-associated infective diarrhoea. The infection is mediated by the spore, a metabolically inactive form of C. difficile . The spore coat acts as a physical barrier to defend against chemical insults from hosts and natural environments. The composition of spore coat has already been revealed; therefore, the interactive networks of spore coat proteins and the dynamic process of coat assembly are the keys to design strategies to control and cure CDI. This review gives a brief discussion of the signal processing and transcriptional regulation of C. difficile sporulation initiation. Following the discussion, the spore formation is also introduced. Finally, this review mainly focuses on the spore coat assembly, a poorly understood process in C. difficile, and important proteins that have been studied.